(3ZfjI GddHjH MjK dG jhLO WHjHs
(3ChdgG (B:s
(3CeG HYO (B: (3abO LeYJ ai gPG GdcJGH efGaY GdbThQ GdJi JQei Ydi GdCQV hGdfHGJGJ s
(3BNQgG (B:s
(3Cf GdfHi (B((3U(B) (3cGf EPG GcJMd GcJMd ai Gdjejf KdGKg jHOC HgG hjNJe HgG , hai GdjSQi CKfjf s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdWH (B- (3bSe GdcJGH GdChd (B- (3U (B132 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3WH (B77) s
Keywords: (3GdWHs